Political Asymmetry and Systems of Information and Social Organization: A Characterization. (1st September 2016) - Castañeda, Renny Rueda
Abstract : This article aims to develop a taxonomy and a further definition of the concept of political asymmetry for operationalization into social science research inquiry. On the one hand the article accounts the single main categories to offer a taxonomy of the concept, exposing the semantic context of symmetry and asymmetry, and depicting the idea of the political sphere from a classical Aristotelian tradition as well making use of public political science and philosophy of law. Later on, drawing on contributions of critical constructivism and particularly Habermas communicative action theory, the article depicts how political asymmetry can be found in contemporary social structures at the level of subsystems of administration such as institutions as well as at the level of individual interaction. The question this article aims to address is how political asymmetry can be represented for political science, and how it can be further operationalized for organizational and social research inquiry. The concept of political asymmetry is taken into account since it is often isolated on debates regarding the way in which institutions transforms historically, and how such settings affect normative constructions enacted and developed within contemporary governance structures. On the other hand it aims to reflect about its role over governance practices that avoid to ensure free and enough interaction within political actors with different cultural baggage and normative representations.